Analysis of the IGF-system in milk from farm animals – Occurrence, regulation, and biomarker potential. (August 2017) - Meyer, Zianka; Höflich, Christine; Wirthgen, Elisa; Olm, Sven; Hammon, Harald M.; Hoeflich, Andreas
Abstract: IGFs and IGF-binding proteins (IGFBPs) are abundantly present in milk and in dairy products. Compared to the IGFs, the IGFBP have received less attention in milk, although truncated IGFBPs and IGFBP-glycosylation have been described in milk. Thereby, complex control of local IGF-effects can be assumed on the levels of IGFBPs, proteases, and protease inhibitors. The present review collects the current knowledge both on presence and regulation of IGFs and IGFBPs in milk particularly from dairy animal species. As a rule higher levels of IGF-I, IGF-II, and IGFBPs are measured around parturition if compared to later time-points of lactation. In all farm animal species included in this review, it is found that the relative abundancies of IGFBPs in milk and serum are similar, with IGFBP-3 and -2 characterized by higher concentrations if compared to IGFBP-4 or -5. The concentrations of IGFs and IGFBPs in milk or dairy products can be altered by hormones, dairy processing, or fermentation. Because milk can be used for non-invasive biomarker research, quality management, and health monitoring, we discuss novel directions of IGF-analysis and potential on-site biomarker research in milk. Highlights: The present knowledge on the occurrence of IGFs and IGFBPs in milk of farm animals has been collected in two separate tables Regulation of the IGF-system in milk and dairy products has been reviewed Biomarker potential of the IGF-system in milk is critically discussed